2013
DOI: 10.1166/jnn.2013.8086
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sedimentation and Dissolution on the Cytotoxicity of Ag Nanoparticles

Abstract: Nanoparticles (NPs) are being employed for various industrial purposes with increasing frequency, yet the adverse health effects associated with the prolonged exposure of humans and the environment to NPs has not been well-established. Particularly, the effects of the extrinsic (or dynamic) physicochemical properties of NPs in aqueous cell culture media (e.g., hydrodynamic size, aggregation, agglomeration, sedimentation, and dissolution of nanoparticles) on the cytotoxicities of the NPs are barely understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…6 The characteristic UV-vis spectrum of the Ag NPs was also observed with an absorption maximum at a wavelength of 400 nm; in addition, the good dispersion stability of the Ag NPs in DMEM cell culture media was also confirmed in a previous study. 6 The MTT cell viability assays performed for the Ag NPs are presented in Figure 1(a), which show a typical dosedependent decrease in cell viability. As shown in Figure 1(b)-(d), cell rounding and reduced cell populations were observed for the cells exposed to higher doses of Ag NPs (10 and 20 g/mL), while in the control cells, cytoid-shaped cells clustered near each other and adhered well to surfaces.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…6 The characteristic UV-vis spectrum of the Ag NPs was also observed with an absorption maximum at a wavelength of 400 nm; in addition, the good dispersion stability of the Ag NPs in DMEM cell culture media was also confirmed in a previous study. 6 The MTT cell viability assays performed for the Ag NPs are presented in Figure 1(a), which show a typical dosedependent decrease in cell viability. As shown in Figure 1(b)-(d), cell rounding and reduced cell populations were observed for the cells exposed to higher doses of Ag NPs (10 and 20 g/mL), while in the control cells, cytoid-shaped cells clustered near each other and adhered well to surfaces.…”
Section: Resultssupporting
confidence: 68%
“…Prior to investigating the effects of flow rate on the cytotoxicity of Ag NPs, we characterized their physicochemical properties. 6 The core size distribution of the Ag NPs used in this study was found to be 8.3 ± 1.5 nm, and the particles were found to have a spherical shape. 6 The characteristic UV-vis spectrum of the Ag NPs was also observed with an absorption maximum at a wavelength of 400 nm; in addition, the good dispersion stability of the Ag NPs in DMEM cell culture media was also confirmed in a previous study.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations